STRATEGI PROMOSI GRESIK ENGLISH CENTER DALAM MENINGKATKAN JUMLAH PESERTA DIDIK BARU MELALUI MEDIA SOSIAL INSTAGRAM - Romadlon, Ahmad Dani; Hakimah, Ema Nurzainul; Paramitha, Dyah Ayu (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the promotional strategies employed by Gresik English Center (GEC) through Instagram, identify the supporting and inhibiting factors in their implementation, and formulate effective promotional strategies to increase new student enrollment. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with the institution owner, social media administrator, tutors, and students, supported by observation and documentation of GEC’s Instagram promotional activities. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that GEC’s promotional strategy focuses on presenting authentic, informative, and educational visual content by utilizing Instagram features such as feeds, stories, and reels. Supporting factors include the quality of learning services, the involvement of internal stakeholders, and content that genuinely represents the learning experience, while inhibiting factors involve limitations in human resources, time management, and content consistency. Effective promotional strategies are characterized by content authenticity, consistency of promotional messages, and responsive interaction with the audience. This study contributes theoretically to the discourse on digital promotion in non-formal education and provides practical insights for English course institutions in optimizing social media–based promotional strategies.